Application of ICT-Based New Instructional Paradigm Used by Teachers - Sa’imah, Sa'imah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose of this study is to describe instructors' abilities to apply a new ICT-based learning paradigm. Data gathering methods include interviews, documentation, observation, and a review of the literature. The descriptive qualitative analysis was performed to analyze the data. Teachers are now expected to be capable of carrying out ICT-based learning. Teachers confront several challenges while establishing ICT-based learning, including: the various circumstances of pupils and aspects of teaching experience, the capacity to operate learning media; and the availability of school infrastructure. Teachers must be able to use material from the internet as well as teacher discussion forums to overcome obstacles in the development of a new ICT-based learning paradigm.